2003
DOI: 10.1002/hup.506
|View full text |Cite
|
Sign up to set email alerts
|

Schneiderian first‐rank symptoms associated with fluvoxamine treatment: a case report

Abstract: This communication describes a patient who developed Schneiderian first-rank symptoms in the course of treatment with fluvoxamine. The patient, a 28-year-old man suffering from panic disorder, developed several first-rank symptoms during fluvoxamine administration. These symptoms abated 1 week after fluvoxamine treatment was discontinued and haloperidol was started. Although haloperidol was discontinued, no further hallucinations or delusions occurred. This finding suggests that fluvoxamine can precipitate Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In cases of clinical and excessive dosage, many previous reports have demonstrated that selective serotonin reuptake inhibitors (citalopram, escitalopram, fluoxetine, fluvoxamine, paroxetine, and sertraline) can cause hallucinations and other psychiatric symptoms. [12][13][14][15][16][17][18][19][20][21] Some previous reports have demonstrated that selective serotonin reuptake inhibitors can lead to these symptoms by causing a pharmacological increase in the dopaminergic neurotransmission that occurs through direct dopamine reuptake blocking or stimulation of the postsynaptic 5-HT 2 and 5-HT 3 receptors. 21,22 This serotonergic neurotransmission function may induce hallucinations.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of clinical and excessive dosage, many previous reports have demonstrated that selective serotonin reuptake inhibitors (citalopram, escitalopram, fluoxetine, fluvoxamine, paroxetine, and sertraline) can cause hallucinations and other psychiatric symptoms. [12][13][14][15][16][17][18][19][20][21] Some previous reports have demonstrated that selective serotonin reuptake inhibitors can lead to these symptoms by causing a pharmacological increase in the dopaminergic neurotransmission that occurs through direct dopamine reuptake blocking or stimulation of the postsynaptic 5-HT 2 and 5-HT 3 receptors. 21,22 This serotonergic neurotransmission function may induce hallucinations.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is unclear whether paroxetine tends to induce nightmares, any drugs associated with norepinephrine, serotonin, or dopamin can induce nightmares 3 . Indeed, there are a number of reports suggesting the hallucinogenic potential of SSRIs 4–20 . A number of patients who have taken SSRIs combined with other neuroactive drugs or have had organic brain dysfunction have presented with hallucinations 4,5,7–10,15–19 .…”
Section: Discussionmentioning
confidence: 99%